Parenting Parents Toward The Twins in Tambakromo Pati - Dewi, Karisma Andam (BELIA: Early Childhood Education Papers, 2016)
The existence of twins is an exceptional phenomenon because there are two or more individuals who have similarities. In parenting and caring for twins, parents of twins will give them same treatment; feed, clothes, bed and others. If this happend continuously, it will have a negative impact, (e.g lack of confidence, lack of self/dependence, lack of the self-understanding) both twins in the future. This condition also happen parents of twins in the Tambakromo Pati. This study aimed to describe and determine the pattern of parenting that is applied to the twins in Tambakromo, Pati. This study used qualitative research methods. Researcher collected data using observation, interviews, and documentation. Validity of data measured using triangulation techniques, methods and timing. Data analysis was carried out interactively and continuously until the data is saturated by the step of data collection, data reduction, data presentation and conclusion. The results of this research are applied to the sixth twins’s parents in Tambakromo, Pati. It uses democratic and authoritarian parenting. Parents applying nurture democratic twins in most aspects of the parenting; eating, drinking, dressing, deliver goods and toys, play, learn, bowel and bladder, achievement, child behavior, parental attitudes, and togetherness of the parents toward their twins. While the authoritarian parenting styles applied in some aspects of the parenting; bathing, sleeping, studying, and the attitude of parents who always get their children always together in daily activities.